AB0741 Multidimensional Health Related Quality of Life Assessment Using PROMIS (Patient Reported Outcome Measurement Information System) Measures in Psoriatic Arthritis Flares. (10th June 2014) - Orbai, A.-M.; Bartlett, S.; Duncan, T.; de Leon, E.; Jones, M.; Bingham, C.O.
Abstract : Background: Psoriatic arthritis (PsA) impacts health and health related quality of life (HRQL). Patients (pts) with PsA have periods of exacerbation or flares, but there is limited characterization from the pt's perspective. PROMIS is an IRT calibrated item bank covering physical, mental, and social health with population-normalized T scores (Mean 50, SD 10). PROMIS measures provide precise estimates using computer adaptive tests (CAT). PROMIS evaluation in specific diseases is limited and not studied in PsA. Objectives: To gather preliminary data on HRQL in PsA patient-reported flare using multiple PROMIS measures. Methods: Participants with PsA completed 10 PROMIS CATs (pain interference, fatigue, physical function, sleep disturbance, sleep related impairment, depression, anxiety, anger, ability to participate social, satisfaction social roles) administered on a tablet. Routine PROs were collected (pt global/pain/fatigue VAS, mHAQ, and flare self-report). Results: We report on the first 42 pts with PsA: White 90%, Female 63%, Mean (SD) age 49 (11) yrs, PsA duration 14 (9) yrs. In the overall PsA population [mean CDAI 7.6 (9)] PROMIS pain interference, fatigue, function and sleep were worse than population norms. Pts reporting PsA flare (n=15) had worse scores across all PROMIS domains compared to no flare (n=27), with statistically significant differences for most domains tested (see Table). Conclusions: These preliminary data on PROMIS CAT assessments of physical, mental, and social health in PsA, which provide population normalized estimates, suggest pts with PsA and self-reported flare suffer impairment in health and HRQL areas encompassing pain, fatigue, function, sleep, mood and participation. PROMIS CATs may help differentiate flare vs non flare states in PsA. Our results highlight impact of PsA on HRQL areas not traditionally assessed in clinical care and research. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1131